The Role of Sports Diplomacy in International Relations : Case study of the Tokyo 2020 Olympic Games - Starilova, Anna (2023)
In 2013 Japan won the bid to host the Tokyo 2020 Olympic Games. Japanese government officials and the IOC were involved in the process of organizing and hosting the event amidst the numerous adversities, such as natural cataclysms in Japan (e.g., the Tohoku earthquake, followed by a tsunami and damage to the Fukushima nuclear plant), the outbreak of the Covid-19 Pandemic, and postponement of the Olympic Games for a year. Therefore, the organizing party had to employ multiple sports diplomacy tools to promote a positive image to global society, engendering new dialogues and making Japan an attractive destination to foreign visitors. The study aimed to showcase the impacts of hosting the sporting mega-event, such as the Olympic Games, and its effects on Japan’s economic, political, and socio-cultural development. In order to achieve the set goal, relevant materials addressing the topic of sports diplomacy and the Olympic Games were gathered. Furthermore, comparative and qualitative research methodologies were selected and employed to analyze the case study of Tokyo 2020. The presented analysis showed that despite postponing the Games and restrictions placed to prevent the spread of Covid-19, Japan managed to successfully host the Tokyo 2020 Olympic Games through the strategic use of sports diplomacy tools and its actors. Moreover, Japan set new trends for hosting future Olympic Games, such as making the structure of the Olympic Games more flexible and accommodating to the actors of sports diplomacy and for the spectators, as well as raising public engagement through social media, volunteering, and various cultural programs.